Increased expression of Drosophila Sir2 extends life span in a dose-dependent manner. - Whitaker, R.; Faulkner, S.; Miyokawa, R.; Burhenn, L.; Henriksen, M.; Wood, J.G.; Helfand, S.L. (Aging, 2013)
Sir2, a member of the sirtuin family of protein acylases, deacetylates lysine residues within many proteins and is associated with lifespan extension in a variety of model organisms. Recent studies have questioned the positive effects of Sir2 on lifespan inDrosophila. Several studies have shown that increased expression of the Drosophila Sir2 homolog (dSir2) extends life span while other studies have reported no effect on life span or suggested that increased dSir2 expression was cytotoxic. To attempt to reconcile the differences in these observed effects of dSir2 on Drosophila life span, we hypothesized that a critical level of dSir2 may be necessary to mediate life span extension. Using approaches that allow us to titrate dSir2 expression, we describe here a strong dose-dependent effect of dSir2 on life span. Using the two transgenic dSir2 lines that were reported not to extend life span, we are able to show significant life span extension when dSir2 expression is induced between 2 and 5-fold. However, higher levels decrease life span and can induce cellular toxicity, manifested by increased expression of the JNK-signaling molecule Puc phosphatase and induction of dnaJ-H. Our results help to resolve the apparently conflicting reports by demonstrating that the effects of increased dSir2 expression on life span in Drosophila are dependent upon dSir2 dosage.